Avaliação das mudanças socioambientais decorrentes da atividade turística em Serra Negra – Bezerros/PE – pelo método GTP - Lemos, Jeferson Emanuel de (2020)
Human activities have increasingly impacted the functioning of the Earth-world system, and it’s fundamental to carefully analyze the alterations in land use and changes in landscapes. Tourism is part of these actions that have influenced in the environmental, but also social balance. Based on these principles, the aim of this work was to carry out an evaluation of the socioenvironmental changes occurred in the last decades, resulting from the tourist activity in Serra Negra, an altitude swamp located in the rural area of the municipality of Bezerros, Pernambuco, through procedures based on the GTP method (Geosystem-Territory-Landscape). For this purpose, in this study, some steps were adopted, which helped to achieve the desired aims. For studies related to environmental dynamics, we have opted to evaluate an element that composes the geosystem, vegetation. In this way, satellite images were analyzed, which made it possible monitoring deforestation, exposure and soils erosion, using data from the TM sensor of the Landsat 5 and Landsat 8 satellites. The multitemporal survey of the Serra Negra vegetation cover was made from the images of the above system, referring to the years 1992, 2007 and 2018. For the territorial dynamics, in addition to bibliographic research about public policies that encouraged the practice of tourism in the region, questionnaires were applied with residents. For the dynamics related to the landscape, questionnaires were also applied, as well as open interviews were conducted with the oldest residents in order to, through the relationship of their representations with the historical facts occurred over the years, understand and better explain whether the changes occurred in the landscape/place were significant. The interviews were carried out with about 10% of the traditional populations of the village. In relation to the environmental framework, it can be verified that there was a significant increase of the degraded areas on the whole analyzed perimeter over the period, which comprises, more or less, the last two decades. In territorial, political, economic issues, it was confirmed that there was an improvement in income and in the creation of jobs for the traditional population, however, there was an exodus of ancient residents due to the lack of knowledge of the implementation plans to tourism in the region and due to lack of clarification/support of the public power, which contributed to the properties, at the beginning, were sold at low cost. Regarding the landscape, there were divergent feelings and perceptions of the place, in other words, at the same time that the subjects feel good in Serra Negra for its natural and social characteristics, such as the pleasant climate and the tranquility of the place, describe, with a certain discouragement, that the village gets “deserted” during weekdays, due to the sale of most houses to second home properties, that only visit the place on weekends, holidays or festive periods. This way, it’s important that negative impacts, environmental or social, are alleviated, with the appropriate precautions by the involved bodies, counting on the participation of the population in the decision making process.